2004
DOI: 10.1177/0091270004263046
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Control and Nephroprotection in Diabetes

Abstract: Achievement of recommended levels of blood pressure as prescribed by guidelines (i.e., systolic blood pressure of < 130 mmHg in people with nephropathy secondary to type 2 diabetes) generally requires three or more different antihypertensive agents that have complementary modes of action. This systolic goal blood pressure, recommended by generally all international guideline committees, was derived from largely observational studies demonstrating a greater reduction of cardiovascular risk and preservation of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…There were smaller decreases in the use of medications that we did not expect to be responsive to the surgery. Patients without diabetes had a greater reduction in their use of antihypertensive medications than patients with diabetes, which could be due to physicians' more aggressive treatment of hypertension in patients with diabetes for nephroprotection or for prevention of cardiovascular complications [12]. Our use of a comparison group strengthens the evidence that the changes observed were causally related to the surgery rather than to secular changes or due to how pharmacy claims were recorded or our method for counting medications.…”
Section: Commentmentioning
confidence: 52%
“…There were smaller decreases in the use of medications that we did not expect to be responsive to the surgery. Patients without diabetes had a greater reduction in their use of antihypertensive medications than patients with diabetes, which could be due to physicians' more aggressive treatment of hypertension in patients with diabetes for nephroprotection or for prevention of cardiovascular complications [12]. Our use of a comparison group strengthens the evidence that the changes observed were causally related to the surgery rather than to secular changes or due to how pharmacy claims were recorded or our method for counting medications.…”
Section: Commentmentioning
confidence: 52%
“…140 mm Hg in not more than 60-70% of the patients, while diastolic BP normalization was reported in 1 90% of the patients. According to Abbott et al [14] , systolic BP values ! 130 mm Hg are achieved in only 11% of the treated hypertensive DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…130 mm Hg are achieved in only 11% of the treated hypertensive DM patients. The inadequate control of hypertension also contributes to the progression of diabetic nephropathy [14] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Achieving target blood pressure is of utmost importance for improving renal outcomes, as reduction in blood pressure is known to exert a nephroprotective effect. 3,15,16 In these patients with renal dysfunction, mean trough plasma aliskiren concentrations increased with dose and reached steady state 2-4 weeks after the start of dosing or up-titration of the dose. The results from an earlier study assessing the effects of renal impairment on pharmacokinetics of aliskiren (300 mg once daily) in patients with mild-to-moderate renal dysfunction and healthy volunteers showed that although exposure is increased by renal impairment, the increase in exposure does not correlate with the severity of renal impairment.…”
Section: Discussionmentioning
confidence: 99%